Characterizing the gut (Gallus gallus) microbiota following the consumption of an iron biofortified Rwandan cream seeded carioca (Phaseolus Vulgaris L.) bean-based diet. - Spenser Reed; Hadar Neuman; Raymond P Glahn; Omry Koren; Elad Tako (PLoS ONE)
Biofortification is a plant breeding method that introduces increased concentrations of minerals in staple food crops (e.g., legumes, cereal grains), and has shown success in alleviating insufficient Fe intake in various human populations. Unlike other strategies utilized to alleviate Fe deficiency, studies of the gut microbiota in the context of Fe biofortification have not yet been reported, although the consumption of Fe biofortified staple food crops has increased significantly over time. Hence, in this study, we performed a 6-week feeding trial in Gallus gallus (n = 14), aimed to investigate the alterations in the gut microbiome following administration of an Fe biofortified bean-based diet (biofortified, BFe) versus a bean based diet with poorly-bioavailable Fe (standard, SFe). Cream seeded carioca bean based diets were designed in an identical fashion to those used in a recent human clinical trial of Fe biofortified beans in Rwanda. We hypothesized that the different dietary Fe contents in the beans based diets will alter the composition and function of the intestinal microbiome. The primary outcomes were changes in the gut microbiome composition and function analyzed by 16S rRNA gene sequencing. We observed no significant changes in phylogenetic diversity between groups. There were significant differences in the composition of the microbiota between groups, with the BFe group harboring fewer taxa participating in bacterial Fe uptake, increased abundance of bacteria involved in phenolic catabolism, and increased abundance of beneficial butyrate-producing bacteria. Additionally, depletion of key bacterial pathways responsible for bacterial viability and Fe uptake suggest that improvements in Fe bioavailability, in addition to increases in Fe-polyphenol and Fe-phytate complexes due to biofortification, led to decreased concentrations of cecal Fe available for bacterial utilization. Our findings demonstrate that Fe biofortification may improve Fe status without negatively altering the structure and function of the gut microbiota, as is observed with other nutritional methods of Fe supplementation. These results may be used to further improve the efficacy and safety of future biofortification efforts in eradicating global Fe deficiency.